African Subregional Mechanisms for Providing Information Privacy: a General Description - Serohin, V. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
african subregional mechanisms for information privacy providing are summarized (within the Economic Community of West African States, the Southern African Development Community, the East African Community, the Economic Community of Central African States, and the Economic and Monetary Community in Central Africa). It has been substantiated that the development of national personal data protection legislation in parallel with model laws at the subregional level is an effective way to promote information privacy.